Energy Analysis of Steam Cycle Efficiency with Feed Water Heater Modification (Case Study: PT. Pertamina EP Asset 1 Field Lirik) - Romy Romy; Muhammad Rizki (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
The increasing energy efficiency program will decrease the consumption of energy. If these improvements are carried out together, it will certainly ensure energy reliability for a sustainable and better future. The aim of this paper was to investigate the possibility of increasing efficiency in the crude oil heating system at PT. Pertamina EP Asset 1 Lirik Field. The research method was done by modification the steam cycle using the close and open Feed Water Heater (FWH). As result, the efficiency of steam cycle of close FWH increased 2.53% and 2.78% for open FWH. While the efficiency of the steam cycle in the initial conditions was 36.74%.